The egg and I - MacDonald, Betty Bard. (New York : Perennial Library, 1987)
The author relates the joys and frustrations of life on a poultry fa rm in the mountains of Washington.
Keywords: MacDonald, Betty Bard; Farm life -- Washington (State); Authors, American -- 20th century -- Biography..; Farmers; Farm life -- Wit and humor; Washington (State) -- Biography